AKTIVITAS ANTIBAKTERI ISOLAT FUNGI ENDOFIT BIJI LABU KUNING (Cucurbita moschata ex. Poir) - Nuryanti, Siska; Fitriana, Fitriana; Ohorella, Fitriah Anggraini (Fakultas Farmasi UMI, 2023)
Cucurbita moschata ex. Poir are one of the medicinal plants that have many benefits, including antidiabetic, antifungal, antibacterial, anti-inflammatory, and antioxidant effects. The content of compounds in yellow pumpkin seeds, such as phenols, alkaloids, and triterpenoids, This study aims to isolate endophytic fungi from yellow pumpkin seeds and test the antibacterial activity of isolates of yellow pumpkin bii endophytic fungi using the Agar diffusion method. The results of the isolation of yellow pumpkin seed endophytic fungi obtained 3 isolates, followed by macroscopic examination and fermentation of the 3 isolates with Maltose Yeast Broth (MYB) media and testing antibacterial activity by Agar diffusion method. Based on the results of the study, 3 isolates with the codes IJBL1, IJBL2, and IJBL3 were obtained that have antibacterial potential. The highest inhibitory zone was produced by IJBL3 endophytic fungi isolate with an inhibitory zone diameter of 12.39 mm against Staphylococcus aureus bacteria